2019
DOI: 10.1021/acs.joc.9b01833
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Bromo-N-heterocycles through Dibromohydantoin-Promoted Tandem C–H Amination/Bromination

Abstract: Herein, we report a metal-free radical tandem C–H amination and bromination reaction with dibromohydantoin (DBH) as both the amination and bromination reagents and water as the main solvent. The reaction involves in intramolecular C–H amination and electrophilic bromination using cheap commercially available DBH. The products represent heterocyclic building blocks, readily modifiable by classical cross-coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Ma et al . also developed an alternative methodology [39] for bromination using DBH as the bromine source instead of NaBr/PhI(OAc) 2 or K 2 S 2 O 8 [38] in a transition metal‐free step‐economic methodology for amination/bromination process.…”
Section: Transition Metal‐free C(sp2)−h Bond Halogenation In Arene Systemsmentioning
confidence: 99%
“…Ma et al . also developed an alternative methodology [39] for bromination using DBH as the bromine source instead of NaBr/PhI(OAc) 2 or K 2 S 2 O 8 [38] in a transition metal‐free step‐economic methodology for amination/bromination process.…”
Section: Transition Metal‐free C(sp2)−h Bond Halogenation In Arene Systemsmentioning
confidence: 99%
“…[16] In light of the above results, we next tended our attention to the tandem intramolecular CÀ H amination and bromination of 2-biaryl phosphamides to synthesize 5'-bromodibenzophosphamides. [17] After a series screening of hypervalent bromine reagents (including N-bromosuccinimide (NBS), dibromohydantoin (DBH) and tribromoisocyanuric acid (TBCA), we found that DBH was the most efficient reagent and the 5'-bromo-dibenzophosphamide was obtained Scheme 1. Methods for the synthesis of N-heterocycle compounds.…”
Section: Synthesis Of Chiral Benzophosphinamidesmentioning
confidence: 99%
“…It is interesting that the dibromo-dibenzophosphamides were also obtained when 3.0 equivalent DBH was used in CH 3 CN (Scheme 5). [17] If the substituent was electrondonating methoxyl, we obtained the tribromo-phosphamide. While when the 4'-CF 3 -substituted substrate was used, the corresponding monobromo-phosphamide was isolated in good yield.…”
Section: Synthesis Of Chiral Benzophosphinamidesmentioning
confidence: 99%
See 2 more Smart Citations